Structural changes in the silver-carbon composite anode interlayer of solid-state batteries - Spencer-Jolly, D; Agarwal, V; Doerrer, C; Hu, B; Zhang, S; Melvin, DLR; Gao, H; Gao, X; Adamson, P; Magdysyuk, OV; Grant, PS; House, RA; et al. (Cell Press, 2023)
Ag-carbon composite interlayers have been reported to enable Li-free (anodeless) cycling of solid-state batteries. Here, we report structural changes in the Ag-graphite interlayer, showing that on charge, Li intercalates electrochemically into graphite, subsequently reacting chemically with Ag to form Li-Ag alloys. Discharge is not the reverse of charge but rather passes through Li-deficient Li-Ag phases. At higher charging rates, Li intercalation into graphite outpaces the chemical reactions with Ag, delaying the formation of the Li-Ag phases and resulting in more Li metal deposition at the current collector. At and above 2.5 mA·cm−2, Li dendrites are not suppressed. Ag nanoparticles do not suppress dendrites more effectively than does an interlayer of graphite alone. Instead, Ag in the carbon interlayer results in more homogeneous Li and Li-Ag formation on the current collector during charge.